THE CONCEPT OF ZUORDNUNG (JOINING) IN KARL LAURENZ’S JURISPRUDENCE OF EVALUATION AND ROBERT ALEXY’S THEORY OF RATIONAL DISCOURSE - BUNCHUK, OKSANA (Ehrlich’s Journal, 2023)
The article analyzes the notions of “Zuordnung” in K. Larenz and R. Alexy as, respectively, the addition of a fact, literally: a life process, the circumstances of a case, to a type, that is, to a non-semantic norm, and the addition of new norms to already established norms. The purpose of the study was to determine the meaning of the term “Zuordnung” in the jurisprudence of K. Larenz’s assessments and R. Alexy’s theory of rational legal discourse. Four questions are considered: about the lexical meaning of the word “Zuordnung” in German and the methods of its translation into Ukrainian, about the concepts of inclusion in K. Larenz and R. Alexy, as well as about the relationship between these concepts. In the first case, it is stated that the word “Zuordnung” in German is a tracing of the Latin word “coordinatio”, and in Ukrainian it can potentially be translated, depending on the context, in several ways, in particular, the words “combination”, “subordination”, “coordination”, “assignment” and “attachment”. Of these options, which do not coincide in everything, the word “attachment” can best convey the meaning that both K. Larenz and R. Alexy mainly put into the concept of “Zuordnung”. The study of the concept of attachment in K. Larenz demonstrates that the author uses the word “Zuordnung” initially in three aspects: in the structure of the legal norm as the attachment of the actual composition of the norm to the legal consequence of the norm; in the theory of types as the attachment of a life process or the circumstances of a case to a type and within the framework of the analysis of the so-called concrete-general concept, which is closely related to Hegel’s philosophy. Later addition in K. Larenz is associated mainly with the theory of types. This leads to the fact that attachment is primarily an alternative to subsummation and consists in the coordinating conjunction of fact and type, which is understood as a normative-empirical form of thinking. As part of the analysis of the concept of inclusion in R. Alexy, it was established that the word “Zuordnung” (attachment) in him has a direct relationship, as can already be seen from the term he chose, to the formation of the so-called “attached norms”. In this case, the addition, as well as the coordinating conjunction, but not the fact and (normative real) type, but the norm and norm, consists in adding new norms to the positive legal system: either the addition of principles that were legally invalid before that, or the addition of rules based on a weighing of principles. Therefore, in R. Alexy, inclusion is a prerequisite or a complement to subsumption, as well as the result of correct reasoning. The latter indicates why in the theory of rational legal discourse (argumentation, justification) so much attention is paid to joining. As a result of the comparison of the concepts of inclusion in K. Larenz and R. Alexy, it is noted that these concepts are alternative, and therefore the use of one approach leads to the leveling of the applied value of the other. R. Alexy’s concept of inclusion as a so-called external justification, which in complex cases is a prerequisite for subsumption (internal justification), has an advantage over K. Lorenz’s concept of inclusion as an alternative to subsumption of internal justification. This is explained by the fact that the first approach leads to operating with a norm capable of subsumption as a result, and the second – to operating as such incapable of subsumption, as a matter of fact, a norm-type. Therefore, the addition of K. Larenz takes place instead of subsumation, and the addition of R. Alexy along with subsumption and to it.